2007
DOI: 10.1016/j.biopsych.2006.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Laboratory-Observed Preschool Behavioral Disinhibition at Five-Year Follow-up

Abstract: Objective-"Behavioral disinhibition" refers to a temperamental tendency to exhibit boldness, approach, and spontaneity in unfamiliar situations. We previously found it to be associated with childhood disruptive behavior and mood disorders as well as with parental bipolar disorder. In the present study, our objective was to examine the diagnostic outcome in middle childhood of behavioral disinhibition assessed at preschool-age among offspring at risk for anxiety and mood disorders.Method-The sample consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 66 publications
(65 reference statements)
1
18
0
Order By: Relevance
“…Inhibited temperament has been the main focus of studies of temperament given its association with anxiety disorders and depression; however, uninhibited temperament is also associated with psychopathology, including attention deficit hyperactivity disorder (ADHD), bipolar disorder, and substance use disorders (Hirshfeld-Becker et al, 2007, 2003, 2002). Much remains unknown about the genetic and neural basis of uninhibited temperament and how these differences may confer risk for psychopathology.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibited temperament has been the main focus of studies of temperament given its association with anxiety disorders and depression; however, uninhibited temperament is also associated with psychopathology, including attention deficit hyperactivity disorder (ADHD), bipolar disorder, and substance use disorders (Hirshfeld-Becker et al, 2007, 2003, 2002). Much remains unknown about the genetic and neural basis of uninhibited temperament and how these differences may confer risk for psychopathology.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Another important point is that most studies compare individuals with an inhibited temperament to those with an uninhibited temperament. while this extreme groups approach provides statistical power, it does raise questions about whether the uninhibited control group is the same as a standard “healthy control group”, since uninhibited children are at risk for developing externalizing disorders (Hirshfeld-Becker et al, 2007, 2003, 2002). To understand the potential impact of using extreme temperament groups, we have recently examined two different datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, teacher ratings of surgency have been associated with greater peer ratings of girls’ “wild behavior” in kindergarten (Berdan, Keane, & Calkins, 2008). Furthermore, studies of disinhibition (i.e., novelty-seeking and impulsivity) have found associations with externalizing/antisocial diagnoses (Hirshfeld-Becker, Biederman, Faraone, Violette, Wrightsman & Rosenbaum, 2002; Hirshfeld-Becker, Biederman, Henin, Faraone, Cayton & Rosenbaum, 2006; Hirshfeld-Becker et al, 2007). …”
Section: Longitudinal Stability Of Temperamental Exuberance and Sociamentioning
confidence: 99%
“…Hirshfeld-Becker and colleagues (Hirshfeld-Becker et al, 2007) have found approach to be directly related to externalizing disorders such as oppositional disorder. In addition, however, combinations of approach and inhibitory control have also been linked to problem behavior.…”
Section: Approach Inhibitory Control and Behavior Problemsmentioning
confidence: 99%